2021
DOI: 10.3390/plants10030429
|View full text |Cite
|
Sign up to set email alerts
|

The Response of the Associations of Grass and Epichloë Endophytes to the Increased Content of Heavy Metals in the Soil

Abstract: The rapid development of civilization increases the area of land exposed to the accumulation of toxic compounds, including heavy metals, both in water and soil. Endophytic fungi associated with many species of grasses are related to the resistance of plants to biotic and abiotic stresses, which include heavy metals. This paper reviews different aspects of symbiotic interactions between grass species and fungal endophytes from the genera Epichloë with special attention paid to the elevated concentration of heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 146 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…Epichloë fungi form bioprotective endophytic symbioses with many cool-season grasses, including agriculturally important forage grasses such as PRG. These endophytic associations have a very important influence on plant growth and interaction with environmental stresses [ 49 , 50 , 51 , 52 , 53 ]. In addition, certain studies have shown that Epichloë can reprogram host plant transcription [ 12 , 13 , 14 , 15 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë fungi form bioprotective endophytic symbioses with many cool-season grasses, including agriculturally important forage grasses such as PRG. These endophytic associations have a very important influence on plant growth and interaction with environmental stresses [ 49 , 50 , 51 , 52 , 53 ]. In addition, certain studies have shown that Epichloë can reprogram host plant transcription [ 12 , 13 , 14 , 15 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë fungi form bioprotective endophytic symbioses with many cool-season grasses, including agriculturally important forage grasses such as PRG. These endophytic associations have a very important influence on plant growth and interaction with environmental stresses [49][50][51][52][53]. In addition, certain studies have shown that Epichloë can reprogram host plant transcription [12][13][14][15][54][55][56] Velvet (velA) is an important gene in filamentous fungi that influences several processes such as fungal growth and metabolism and resistance to various stresses [57][58][59][60][61][62] and we have previously reported its importance in the symbiosis of E. festucae with PRG [6,9,38].…”
Section: Discussionmentioning
confidence: 99%
“…and, Fe, Mn, B, Zn, Mo, Cu, respectively, available in the soil. With emphasis on Zn and Cu, necessary for the proper development of living organisms [51], [52]. According to the largest amount of nutrients, present in vegetables, is concentrated in the peels of the fruits and not in the pulp, so the peels can be considered sources of nutrients, which are most often discarded.…”
Section: General Aspects Of Residuesmentioning
confidence: 99%